VIOLENCE AND INSECURITY IN NIGERIA : THE BANE OF NATIONAL DEVELOPMENT - Okeshola, Folashade B. (European Scientific Journal, ESJ, 2014)
Violence breeds insecurity in Nigeria. Lack of security of lives and property of the citizenry is a severe hindrance to meaningful development. A climate of fear will frighten domestic and foreign investors. At the heart of many of these conflicts is access to resources and control over the distribution of benefits. This struggle for resources has led to a broad sense of insecurity, opportunism, and the pursuit of self- help strategies across the country. Some of the causes of violence include god fatherism, poverty, unemployment, money and politics, corruption, small arms proliferation, the rise of armed groups, religious based violence and election fraud. These issues represent dividing lines in communities that have led to heightened tensions between and within groups. This paper will therefore examine the root causes of violence vis-à-vis insecurity, its effects and proffer strategies that will make Nigeria a safe place to live.